Association between eating time interval and frequency with ideal cardiovascular health: Results from a random sample Czech urban population - Maugeri, A; Kunzova, S; Medina-Inojosa, J R; Agodi, A; Barchitta, M; Homolka, M; Kiacova, N; Bauerova, H; Sochor, O; Lopez-Jimenez, F; Vinciguerra, M (Nutrition, metabolism, and cardiovascular diseases, 2018)
BACKGROUND AND AIMS: The frequency and timing of meals may affect cardiovascular health (CVH) outcomes, but large-scale epidemiological studies are lacking. The aim of this study was to understand the relationship between eating time interval and frequency, and measures of ideal CVH in the Kardiovize Brno cohort study, a random urban sample population in Central Europe. METHODS AND RESULTS: 1659 members of the Kardiovize Brno 2030 cohort were included in a cross-sectional study (mean age = 46.86 years; 44.6% male). Exposure variables were eating time interval and frequency, and skipping meals. Primary outcomes were indices of CVH, including body mass index, diet, physical activity, smoking, blood pressure, glucose and cholesterol, and the composite CVH score. Cluster analysis and binary logistic regression analysis were used to evaluate eating habits and the association between variables. After adjustment for well-known risk factors, subjects who skipped breakfast or the afternoon snack had a higher risk of poor CVH (OR = 1.613; 95%CI = 1.121-2.320; p = 0.010; OR = 1.409; 95%CI = 1.110-1.788; p = 0.005, respectively). Moreover, we identified three clusters of individuals based on eating habits; from cluster 1 to cluster 3, eating time interval and frequency increased and this was associated with increases in CVH score from 8.70 (SEM = 0.10) in cluster 1, and 9.06 (SEM = 0.08) in cluster 2 to 9.42 (SEM = 0.09) in cluster 3 (p-trend = 0.019). CONCLUSIONS: Our findings suggest that skipping breakfast or the afternoon snack are risk factors for poor CVH, while higher eating time interval and frequency may promote ideal CVH.
Keywords: Cross-Sectional Studies; stravovací zvyklosti; Male; ochranné faktory; Risk Factors; Healthy Lifestyle; chování snižující riziko; přijímání potravy; Česká republika; Cardiovascular risk factors; Adult; Feeding Behavior; Prospective Studies; dospělí; mužské pohlaví; zdravý životní styl; Eating; Meals; Czech Republic; Time Factors; Urban Health; kardiovaskulární nemoci; Health Status; lidé; jídla; Breakfast; ženské pohlaví; Eating habits; Snack; Humans; Risk Reduction Behavior; časové faktory; rizikové faktory; průřezové studie; zdraví ve městech; zdravotní stav; Skipping meals; Cardiovascular Diseases; Protective Factors; Female; lidé středního věku; Middle Aged; prospektivní studie